Integration of Enculturation and Child Protection through Future Play in Early Childhood Education - Mutiara Magta; Yuliani Nurani; Sri Wulan (Yayasan Keluarga Guru Mandiri, 2026)
Future play is increasingly positioned as a central construct for understanding how early childhood education responds to digital transformation, particularly in relation to learning, enculturation, and child protection. This study aims to map research trends, identify dominant themes, theories, and methodologies, and synthesize evidence on how future play contributes to cultural identity formation, safeguarding, and the development of social value in early childhood settings. A systematic literature review was conducted using a transparent protocol aligned with established standards for evidence synthesis. Fifty peer-reviewed journal articles, indexed in Google Scholar, Scopus, and SINTA-2, and published between 2020 and 2025, were selected and analyzed through a combined bibliometric mapping and thematic synthesis. Results show marked growth in publications post-2021, shifting from gamification/simulation to concerns about socio-cultural identity and the digital environment. Four thematic clusters emerged: digital play in education, enculturation/identity, child protection/mental health, and theory–methodology development, dominated by cultural-historical and subcultural frames. Synthesis across themes shows that future play enhances motivation/learning, inclusion, cultural participation/identity, and protection functions such as well-being, privacy awareness, and family–school co-regulation. Overall, the study positions future play as an integrative paradigm for curriculum innovation, ethical digital design, and rights-based child protection, while emphasizing the need for longitudinal, context-sensitive research on sustained impacts.